2015
DOI: 10.18406/2316-1817v7n42015761
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e diversidade da regeneração florestal na nascente do Córrego São Pedro, Juiz de Fora, MG.

Abstract: ResumoEsse trabalho descreve a composição florística, a estrutura do estrato regenerante arbóreo de um trecho de floresta secundária, na nascente do Córrego São Pedro, na área rural do município de Juiz de Fora, Minas Gerais, Brasil. O manancial foi escolhido devido à sua importância como recurso hídrico, como corredor ecológico e por se tratar de uma Área de Preservação Permanente. Em um trecho que compreende 700 metros, a partir da nascente, foram alocadas 25 parcelas de 5 x 5 m e amostrados todos os indivíd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These endangered species are likewise found in large numbers in other large and well-preserved Semideciduous Atlantic Forests (Dalanesi et al 2004, Marangon et al 2008, but not always as important and frequent as in the present study. The species we found in the understory stratum with greater VI, mainly from the treelet and tree life forms, are also commonly found, mainly in the semideciduous forests fragments, such as the treelet species: Casearia sylvestris, Mabea fistulifera, Roupala montana and Trichilia emarginata; as some of our highest VI shrub species Cordiera elliptica, Cordiera sessilis and Faramea latifolia (Pinheiro et al 2012, Franco et al 2007, Pedreira & Sousa 2011, Lopes et al 2012, Paiva et al 2015, Rotmeister et al 2015, Silva & Mazine 2016. We also found some species that are indicators from mature forest (according Franco et al 2007), such as the tree species: Campomanesia guazumifolia (Cambess.)…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…These endangered species are likewise found in large numbers in other large and well-preserved Semideciduous Atlantic Forests (Dalanesi et al 2004, Marangon et al 2008, but not always as important and frequent as in the present study. The species we found in the understory stratum with greater VI, mainly from the treelet and tree life forms, are also commonly found, mainly in the semideciduous forests fragments, such as the treelet species: Casearia sylvestris, Mabea fistulifera, Roupala montana and Trichilia emarginata; as some of our highest VI shrub species Cordiera elliptica, Cordiera sessilis and Faramea latifolia (Pinheiro et al 2012, Franco et al 2007, Pedreira & Sousa 2011, Lopes et al 2012, Paiva et al 2015, Rotmeister et al 2015, Silva & Mazine 2016. We also found some species that are indicators from mature forest (according Franco et al 2007), such as the tree species: Campomanesia guazumifolia (Cambess.)…”
Section: Discussionmentioning
confidence: 53%
“…Some studies showed that even small forest fragments, most of them in private areas, could maintain high diversity or, at least some plant species from mature forest stage (e.g. Santin 1999, Franco et al 2007, Reis et al 2007, Carvalho & Felfili 2011, Brito & Carvalho 2014, Rotmeister et al 2015. Even small secondary forest fragments are important for conservation, since they present high floristic heterogeneity resulting from environmental variations and the different disturbance degrees to which these forests have been submitted (Sansevero et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levando-se em consideração o observado durante o reconhecimento da área para a realização do estudo, o fragmento em questão localiza-se em posição adjacente a uma área residencial (figura 1) e, com isso, sofre considerável perturbação antrópica, evidenciada por sinais de corte seletivo de madeira em seu perímetro, abertura de trilhas em seu interior e sinais de queimadas eventuais. Esse cenário impõe barreiras, retardando e dificultando a progressão da sucessão florestal, que se reflete tanto nos índices de diversidade quanto na elevada presença de espécies de grupos sucessionais iniciais (FONSECA et al, 2013;ROTMEISTER et al, 2015).…”
Section: Continuação Da Tabelaunclassified
“…Houve predominância de espécies e indivíduos zoocóricos neste trabalho, representando 67,50% e 87,05%, respectivamente (figura 3). Tal padrão também foi observado por Fonseca et al (2013), ao estudar a regeneração de um fragmento urbano, e por Rotmeister et al (2015), em mata ciliar secundária, ambos os trabalhos realizados em Juiz de Fora (MG). A alta representatividade de espécies de dispersão zoocórica pode ser explicada pela relevante contribuição da família Myrtaceae no presente trabalho, visto que seus frutos são dispersos pela fauna, sendo o grupo das aves seu principal dispersor (GRESSLER et al, 2006).…”
Section: Continuação Da Tabelaunclassified